Description of a new species of ltalian Cnephasia Curtis, 1826, from Mount Etna, with notes on the cnephasiine ovipositor (Lepidoptera Tortricidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new species of Italian tortricid moth, Cnephasia etnana sp.n. fromMount Etna, Sicily, is described. Extemally the new species resembles C. abrasana(Duponchel, 1843), or forms of C. constantinana Razowski, 1965, or C. korvaciRazowski, 1965. In male genitalia it is similar to the two last mentioned species,the differences are in the size of terminal plate of the gnathos (mainly in C.korvaci) and the smaller aedeagus; from C. abrasana it strongly differs in thestructure of sacculus. The females of C. etnana and C. abrasana are very similarto one another mainly in the form of the ovipositor and papillae anales whichare slenderer and more simple than in all known species of the subgenusCnephasia s.str. inclusive the two compared species.
Keywords: Lepidoptera Tortricidae; Cnephasia etnana; new species; Italy